Overweight/Obesity in Childhood and the Risk of Early Puberty: A Systematic Review and Meta-Analysis - Zhou, Xuan; Hu, Yang; Yang, Ziqi; Gong, Ziqiang; Zhang, Senmao; Liu, Xiaoling; Chen, Yan; Ye, Changxiang; Chen, Lizhang; Wang, Tingting (Frontiers in Pediatrics, 2022)
Purpose: To determine the relationship between childhood overweight/obesity and early puberty in both boys and girls. Specifically, this is the first time to conduct a meta-analysis of the relationship between childhood overweight/obesity and early puberty in boys. Methods: Relevant studies were identified from PubMed, Web of Science, and EMBASE searches. The exposure of interest was overweight/obesity in childhood. Childhood was defined internationally as the age range of 0-18 years. The overall risk estimates were pooled using random effects models. Subgroup and sensitivity analyses were performed to explore possible sources of heterogeneity and to assess the robustness of the results. Results: A total of 10 studies involving 13,055 girls and 12,454 boys were included. Results showed that childhood overweight/obesity was associated with a significantly higher risk of early puberty in girls (odds ratio [OR]: 2.22, 95% CI: 1.65-2.99). Although without statistical significance, a higher risk of early puberty was also found in boys who were overweight/obese in childhood (OR: 1.29, 95% CI: 0.98-1.70). Heterogeneity in the risk estimates of early puberty was partially explained by study design, sample size, follow-up duration,definitions of early puberty, and confounders controlled. Sensitivity analyses validated the robustness of the findings. Conclusions: Our findings showed that for girls the associate between overweight/obesity and early puberty is definite or strong whereas for males, such an association is possible, prompting that future studies need to further explore the possible relationship between overweight/obesity and early puberty in boys.